2016
DOI: 10.1007/s13762-016-0943-1
|View full text |Cite
|
Sign up to set email alerts
|

A sandwiched denitrifying biocathode in a microbial fuel cell for electricity generation and waste minimization

Abstract: A denitrifying biocathode in a microbial fuel cell was developed to investigate the replacement of the costly Pt-coated abiotic cathodes for electricity generation. The denitrifying biocathode was sandwiched between the dual-anode systems. The study investigated the performance for simultaneous treatment of wastewater on the anode, biological denitrification on the cathode and the potential recovery of electrical energy. Autotrophic biofilms performed denitrification on the cathode using supplied electrons by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…claimed that the maximum power density was 35 W m –3 NCC in cathodic denitrification in an upflow MFC with an internal cathode. In another study by Al‐Mamun et al 65 . in a sandwiched denitrifying MFC, the maximum power density of 7 W m –3 NCC was reported.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…claimed that the maximum power density was 35 W m –3 NCC in cathodic denitrification in an upflow MFC with an internal cathode. In another study by Al‐Mamun et al 65 . in a sandwiched denitrifying MFC, the maximum power density of 7 W m –3 NCC was reported.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Clauwaert et al 18 claimed that the maximum power density was 35 W m -3 NCC in cathodic denitrification in an upflow MFC with an internal cathode. In another study by Al-Mamun et al 65 in a sandwiched denitrifying MFC, the maximum power density of 7 W m -3 NCC was reported. Virdis and co-workers 66 investigated the possibility of simultaneous carbon and nitrogen removal in an H-shaped MFC during cathodic denitrification, and they found that the nitrate concentration in cathode chamber dropped 97.1% at the highest current produced (at external resistance of 5 Ω and C/N ratio of 1.68), and a current density and power density of 133.3 A m -3 NCC and 34.6 W m -3 NCC, respectively, were achieved.…”
Section: Effect Of External Resistance On Performance Of Utmfc At C/nmentioning
confidence: 89%
“…The corresponding power density curve was found from the plot of current density versus power density. The internal resistance of the MFC was determined according to the method reported somewhere else [10] . The COD removal efficiency of the MFC was calculated by employing 2000 mg/L COD wastewater sample in the anodic chamber followed by replacing it with 1500, 1000, and 500 mg/L COD concentrations.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Afterwards, the polarization curve was plotted in terms of current and power denisty vs voltage followed by power density curve which was intialy obtained from the tabulated value of current against power density. The internal resistance of the microbial fuel cell (MFC) was determined according to the method employed for polarization slope method which was reported somwhere else [2 , 3] . The removal efficiency of MFC for each COD concentration of the wastewater sample was calculated using equation (5).…”
Section: Specifications Tablementioning
confidence: 99%
“…To reduce the operating costs there is an urgent requirement for developing improved cathodic aeration devices. At the same time, the use of plant composite bio-cathodes instead of precious metal cathodes as in the conventional CW-MFC, would allow to greatly reduce the electrode material costs, possibly improve the catalytic activity of the electrode and allow for the largescale production of CW-MFCs [6][7][8].…”
Section: Introductionmentioning
confidence: 99%